2019
DOI: 10.3390/beverages5030055
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Preferences for Dairy-Alternative Beverage Using Home-Scan Data in Catalonia

Abstract: The changing lifestyles and the growing health concerns towards the negative impact of the saturated fatty acids originating from animals has increased consumers’ preferences for dairy-alternative products. These products belong to the food and beverage classification that is similar to certain types of dairy-based products in terms of texture and flavor, and has similar nutritional benefits. In this context, we seek to identify the willingness to pay (WTP) for the most important attributes that consumers take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…(2019) reviewed the different compositions in terms of macronutrients and micronutrients of milk from different mammalian species, including special milk formulas indicated for cow's milk allergy, and of dairy alternative beverages. The empirical research about consumer preference on dairy alternative products embraces Laassal and Kallas (2019) who applied revealed preference discrete choice experiment to analyze consumers' preferences toward dairy‐alternative products in Catalonia using Home‐Scan data of 343 households and the results showed that price was the major driving factor, followed by the original non‐dairy beverage flavor attribute. With the elevated demand on plant‐based alternative milk beverages in U.S., Dharmasena and Capps (2014) estimated the demand for soy milk, white milk, and flavored milk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2019) reviewed the different compositions in terms of macronutrients and micronutrients of milk from different mammalian species, including special milk formulas indicated for cow's milk allergy, and of dairy alternative beverages. The empirical research about consumer preference on dairy alternative products embraces Laassal and Kallas (2019) who applied revealed preference discrete choice experiment to analyze consumers' preferences toward dairy‐alternative products in Catalonia using Home‐Scan data of 343 households and the results showed that price was the major driving factor, followed by the original non‐dairy beverage flavor attribute. With the elevated demand on plant‐based alternative milk beverages in U.S., Dharmasena and Capps (2014) estimated the demand for soy milk, white milk, and flavored milk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to capture consumers’ attitude, preferences and motivation toward plant milk and their related influencing factors, some empirical research has sprout up to achieve this goal. Empirical consumer research by Laassal and Kallas (2019) [ 28 ] utilized Homescan data of 343 households and drew on revealed preference discrete choice experiment to evaluate consumers’ propensity to dairy alternative products in Catalonia. The main results implied that price was the principal contributing factor, followed by flavor attribute.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It seems that the health-related characteristics of non-dairy drinks are significant for U.S. consumers. However, a study on consumer preferences towards plant-based dairy beverages conducted in Spain showed that, apart from the price, the product’s flavour was the major driving factor contributing to the utility of plant beverages [ 7 ]. Along with the health, price, and taste characteristics, environmental issues may be another reason why people reach for plant-based dairy alternatives [ 8 ].…”
Section: Introductionmentioning
confidence: 99%